Immune-endocrine network in diabetes-tuberculosis nexus: does latent tuberculosis infection confer protection against meta-inflammation and insulin resistance? - Aravindhan, Vivekanandhan; Yuvaraj, Srinivasan (Frontiers in Endocrinology, 2024)
Tuberculosis patients with diabetes, have higher sputum bacillary load, delayed sputum conversion, higher rates of drug resistance, higher lung cavitary involvement and extrapulmonary TB infection, which is called as "Diabetes-Tuberculosis Nexus". However, recently we have shown a reciprocal relationship between latent tuberculosis infection and insulin resistance, which has not been reported before. In this review, we would first discuss about the immune-endocrine network, which operates during pre-diabetes and incipient diabetes and how it confers protection against LTBI. The ability of IR to augment anti-TB immunity and the immunomodulatory effect of LTBI to quench IR were discussed, under IR-LTB antagonism. The ability of diabetes to impair anti-TB immunity and ability of active TB to worsen glycaemic control, were discussed under "Diabetes-Tuberculosis Synergy". The concept of "Fighter Genes" and how they confer protection against TB but susceptibility to IR was elaborated. Finally, we conclude with an evolutionary perspective about how IR and LTBI co-evolved in endemic zones, and have explained the molecular basis of "IR-LTB" Antagonism" and "DM-TB Synergy", from an evolutionary perspective.